2017
DOI: 10.4274/jcrpe.3525
|View full text |Cite
|
Sign up to set email alerts
|

Neck Circumference to Assess Obesity in Preschool Children

Abstract: Objective:Limited information is available about the use of neck circumference (NC) to assess obesity in preschool children. This study aims to provide NC percentiles and determine the cut-off levels of NC as a measure to assess obesity in preschool children.Methods:The data were obtained from the Anthropometry of Turkish Children aged 0-6 years (ATCA-06) study database. A total of 21 family health centers were chosen and children aged 2-6 years old from all socioeconomic levels were randomly selected from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 32 publications
3
16
0
1
Order By: Relevance
“…The study also demonstrated that NC, WC and BMI are significantly associated with blood pressure, which confirms the observations of the previous findings around the relationship between mean anthropometric parameters and blood pressure values [4,7,17]. However, the precise mechanism by which anthropometric parameters act to increase blood pressure is not fully understood.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The study also demonstrated that NC, WC and BMI are significantly associated with blood pressure, which confirms the observations of the previous findings around the relationship between mean anthropometric parameters and blood pressure values [4,7,17]. However, the precise mechanism by which anthropometric parameters act to increase blood pressure is not fully understood.…”
Section: Discussionsupporting
confidence: 89%
“…Children with BMI <85th, ≥85th and ≥ 95th percentile were considered normal, overweight and obese, respectively [7]. Children with WC ≥90th percentile were considered to have abdominal obesity, and those with NC 90th ≥ were considered to have obesity [3,11].…”
Section: Anthropometrymentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we described for the first time in Mexican children the usefulness of NC for assessing elevated central adiposity, evidenced by its high correlation with WC. Many studies conducted in South America, the USA, Europe and a few Middle Eastern countries have evaluated the validity of NC (7,(22)(23)(24)(25)(26)(27)(28) . These reports have also proposed it as a rapid, easily performed method to identify overweight and obesity.…”
Section: Discussionmentioning
confidence: 99%
“…renowned Framingham heart study reported that NC is an index of central obesity as it associates independently with visceral adiposity and BMI [9]. However, there are only a few studies that provide reference data on NC measurements worldwide [10][11][12]. There is a paucity of nationwide studies regarding the utility of NC in screening obesity in the Indian pediatric population [13,14].…”
Section: Online Firstmentioning
confidence: 99%